Of clowns and gods, Brahmans, and babus: humour in South Asian literature - Oesterheld, Christina; Zoller, Claus Peter (South Asian studies, 1999)
Humour as a competence inherent in all human beings defies description and its huge variety, forms and faces have always engendered curiosity. For centuries people have attempted to pinpoint the essence of humour. The contributors to this volume, however, restrict their study of humour to the written and oral literatures of South Asia. They approach the problems not only intutively, from their own sense of humour, but go beyond that out of a recognition that humour as "performance" is culture specific and cannot, therefore, always be comprehended on the spot. Several contributors cast their work in various theoretical frameworks, particularly theories of humour. The volume contains a broad spectrum of essays on the subject in modern and premodern, in classical and folk, and in written and oral literatures from almost all corners of the subcontinent. They treat the subject from a multitude of perspectives and offer background of different theories of humour. With one exception, the contributions have a common characteristic: they deal with material that has not been explored so far in research. These empirical studies are, therefore, the first step towards a theoretical analysis of humour in South Asia. the multi-regional coverage of papers opens up potential for comparative research on humour in the literature and verbal arts of contemporary South Asia.